Effects of orthokeratology lenses on tear film and tarsal glands and control of unilateral myopia in children - Li, Li; Lai, Taichen; Zou, Jing; Guo, Linling; Lin, Zhiming; Lin, Jiawen; Xue, Ying (Frontiers in Cell and Developmental Biology, 2023)
Introduction: To investigate the effects of an orthokeratology lens on the tear film and tarsal glands and myopia control in children with unilateral myopia using an intelligent analysis model. Methods: We retrospectively reviewed the medical records from November 2020 to November 2022 of 68 pediatric patients with unilateral myopia in Fujian Provincial Hospital who had been wearing an orthokeratology lens for more than 1 year. The 68 myopic eyes were included in the treatment group, while the 68 healthy, untreated contralateral eyes were included in the control group. Tear film break-up times (TBUTs) were compared between the two groups at various intervals, and an intelligent analysis model was used to compare the deformation coefficients of 10 meibomian glands in the central area and the different positions of the glands in the two groups after 12 months of treatment. Changes in axial length and equivalent spherical power were also compared between the groups before and after 12 months of treatment. Results: In the treatment group, TBUTs differed significantly between 1 and 12 months after treatment, although no significant differences from baseline were observed at 3 or 6 months. No significant differences in TBUTs were observed at any time point in the control group. After 12 months of treatment, significant between-group differences were observed for glands 2, 3, 4, 5, 6, 7, 8, and 10 (numbered from the temporal to nasal regions). The treatment group also exhibited significant differences in deformation coefficients at different detection positions in the central region, with glands 5 and 6 exhibiting the highest deformation coefficients. Increases in axial length and equivalent spherical power were significantly greater in the control group than in the treatment group after 12 months of treatment. Discussion: Wearing orthokeratology lenses at night can effectively control myopia progression in children with unilateral myopia. However, long-term use of these lenses may lead to meibomian gland deformation and impact tear film function, and the extent of deformation may vary at different positions in the central region.